Family planning: the importance of knowing the characteristics of the population for implementing health actions - de Jesus Ribeiro, Paula; S. Barros, Karla Helena; Alves dos Reis, Rosa; Souza Leite Campinas, Lúcia de Lourdes (O Mundo da Saúde, 2008)
The aim of this study was to compare the program of family planning (FP) of a Family Health Strategy (FHS) and the profile of the general population regarding the contraceptive method selected (CM) and the outcome, the social-economic-cultural characteristics of subjects, and the adopted CM. It was carried out in a FHS of Guarulhos/SP. Subjects were people who participated in FP in 2006, and the sample was composed by 30 individuals (29 women and 1 man) with ages from 18 to 48 years, a predominance of women both in the population and in the sample. Most subjects had chosen tubal ligation (51.6%; p <0.001). Most sample subjects had ages from 28 to 38 years (50.0%), incomplete elementary education(50.0%; p=0.017), married / living together (90%), an average three children (85.0%) and monthly income from one to three minimum wages (33.3%); preference for IUD (33.3%); pregnancy while using the chosen CM in two cases (6.7%); satisfaction with the CM for 80.0% of the individuals (p <0.001), although 43.3% decided to use other CM and had chosen tubal ligation. There was a preference for a reversible CM among the youngest and a definitive among all others, and most of the latter had had little schooling (p=0.019), were married / living together, with three or more children, with no regular income or earning from one to three minimum wages. We concluded that most participants in the FP program were women, married / living together, having low schooling and low income, with more than a son, and preferring tubal ligation and IUD. The little male participation in FP was compatible with Brazil’s data, confirming the necessity of more investment in programmatic actions directed to “men and FP”.